Which factors are behind Germany's labour market upswing? - Christian Hutter; Sabine Klinger; Enzo Weber; Carsten Trenkler (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
The strong and sustained labour market upswing in Germany is widely recognized. In a developing literature, various relevant studies highlight different specific reasons. The underlying study, instead, simultaneously considers a broad set of factors in a unified methodological framework and systematically weighs the candidate reasons for the labour market upswing against each other on an empirical basis. The candidates are: shocks on (de)regulation of employment or job creation intensity, the efficiency of the matching process, wage determination, the separation propensity, the size of the labour force, technology, business cycle and working time. We develop a structural macroeconometric framework that leaves as manyof the systematic interlinkages as possible for empirical determination while operating with a minimal set of restrictions in order to identify economically meaningful shocks. For this purpose, we combine short- and long-run restrictions based on search-and-matching theory and established assumptions on labour force development and technological change. Matching efficiency, job creation intensity, labour force, and separation propensity yield the largest contributions in explaining the German labour market upswing. – – Der starke und anhaltende Arbeitsmarktaufschwung in Deutschland ist allgemein anerkannt. In einer sich entwickelnden Literatur heben verschiedene relevante Studien unterschiedliche spezifische Gründe hervor. Die vorliegende Studie berücksichtigt stattdessen eine Vielzahl von Faktoren in einem einheitlichen methodischen Rahmen und wägt die potenziellen Gründe für den Arbeitsmarktaufschwung systematisch gegeneinander ab. Die Kandidaten sind: Schocks in Bezug auf die (De-) Regulierung der Beschäfiigung oder die Intensität der Schaffung von Arbeitsplätzen, die Effizienz des Matching-Prozesses, die Lohnfindung, die Entlassungsneigung, das Arbeitsangebot, die Technologie, den Konjunkturzyklus und die Arbeitszeit. Wir entwickeln einen strukturellen makroökonometrischen Rahmen, der die Daten so frei wie möglich sprechen lässt und dabei mit einer minimalen Anzahl an Restriktionen arbeitet, um die wirtschafilich bedeutsamen Schocks zu identifizieren. Zu diesem Zweck kombinieren wir kurz- und langfristige Restriktionen auf der Grundlage von Such- und Matchingtheorie und etablierten Annahmen zur Entwicklung des Arbeitsangebots und zum technologischen Wandel. Matching-Effizienz, Intensität der Schaffung von Arbeitsplätzen, Arbeitsangebot und Entlassungsneigung liefern die größten Beiträge zur Erklärung des deutschen Arbeitsmarktaufschwungs.
Keywords: C32; E24; J21; 330; German labour market upswing; labour force; job creation; deregulation; efficiency; separation propensity